On the occurrence and health risks of the Silver-cheeked Toadfish (Lagocephalus sceleratus Gmelin, 1789) in the marine ecosystem of the Gaza Strip, Palestine - ABDEL FATTAH N. ABD RABOU (Society for Indonesian Biodiversity, 2019)
Abstract. Abd Rabou AFN. 2019. On the occurrence and health risks of the Silver-cheeked Toadfish (Lagocephalus sceleratus Gmelin, 1789) in the marine ecosystem of the Gaza Strip, Palestine. Biodiversitas 20: 2620-2627. The Silver-cheeked Toadfish (Lagocephalus sceleratus Gmelin, 1789) is one of the most recent invaders into the Mediterranean Sea. It represents a serious ecological risk to Mediterranean biodiversity and fisheries resources and a health risk to public health. The current study comes to handle the occurrence and health risks of the species in the Eastern Mediterranean of the Gaza Strip, Palestine. Frequent visits to local fish markets, meetings, and discussions with stakeholders, and chasing of local media reports were the main tools involved to satisfy the goals of the study, which extended from 2010 to 2019. The first record of the Silver-cheeked Toadfish in the Mediterranean coast of the Gaza Strip was in 2006 as claimed by fisheries parties. The by-catch of the species by fishing gear extended over the entire length of the Mediterranean coast of the Gaza Strip (42 km). The species was said to damage fishing nets, lines and hooks by its strong teeth. Prior to its banning in early 2010s, all pufferfishes including the species in question were sold freely in Gaza fish markets. Several cases of hospitalization have been reported in the Gaza Strip after consumption of the Silver-cheeked Toadfish. The symptoms of TTX intoxication included nausea and vomiting, dizziness, headache, abdominal pain, perioral paraesthesia, and tingling over the entire body. No death cases were reported locally. Many awareness campaigns have been conducted by fisheries parties to warn both fishermen and local people from the ecological and health risks associated with the Silver-cheeked Toadfish and TTX intoxication. Finally, the threats imposed by the Silver-cheeked Toadfish on the Eastern Mediterranean countries including Palestine indicate that potential solutions to the problem should be explored.